2018
DOI: 10.1177/1750481318757777
|View full text |Cite
|
Sign up to set email alerts
|

In tragoedia risus: Analysis of dark humour in post-terrorist attack discourse

Abstract: In this article, we examine dark humour in Internet posts commenting on an online Italian newspaper report published by Il Fatto Quotidiano and devoted to the 2016 terrorist attack in Nice. The analysis focuses on the linguistic forms and socio-pragmatic functions of this dark humour in the wake of the tragedy. We argue that the creative humorous posts are meant to communicate Internet users’ ideologies conceptualised as their true beliefs about the sociopolitical situation and that they are oriented primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…The main objective of this study was to investigate the appreciation of the humor inspired by an unprecedented situation, namely the Covid-19 pandemic. Using the methods typical of linguistic and psychological humor studies, we expanded the literature on dark humor, especially in the domain of digital humor and Internet-based communication influenced by tragedies (e.g., Dynel and Poppi, 2018). Our study showed that both form and content shaped the funniness and aversiveness ratings of digital humor circulating on Italian social media.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The main objective of this study was to investigate the appreciation of the humor inspired by an unprecedented situation, namely the Covid-19 pandemic. Using the methods typical of linguistic and psychological humor studies, we expanded the literature on dark humor, especially in the domain of digital humor and Internet-based communication influenced by tragedies (e.g., Dynel and Poppi, 2018). Our study showed that both form and content shaped the funniness and aversiveness ratings of digital humor circulating on Italian social media.…”
Section: Resultsmentioning
confidence: 98%
“…Like many types of humor, Covid-19 humor is also based on an incongruity (Forabosco, 2008(Forabosco, , 1992: the background situation related to the Coronavirus pandemic sets up tragic expectations, which the stimulus diverts from, setting a humorous clash by means of more or less innocuous themes, such as television catchphrases or refrains of songs. With respect to the thematic contents, Covid-19 humor may be considered a form of dark humor, namely the kind of humor that touches upon matters of death or morbid topics and elicits a bitter amusement (Bucaria, 2008;Maxwell, 2003), or that is inspired by traumatic and difficult situations, such as tragedies and background crises (Dynel and Poppi, 2018). To account for the timely rise of humor based on shocking events, some scholars label these forms of humor as "disaster humor" (Kuipers, 2002) since they appear soon after incidents and generally follow the media coverage of the facts (Davies, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuiper et al 1993;Martin 2007), which attests to the famous adage that humor equals tragedy plus time. Relief is a welldocumented function of humor in tragic historical contexts (see e.g., Martin 2007;Martin and Ford 2018), which has recently gained some support with reference to online humor (see Demjén 2016;Dynel and Poppi 2018), and this research adduces further evidence in this regard, focusing on personal misfortunes.…”
Section: Discussion: Theorizing About Shitmyrevierssay Tweetsmentioning
confidence: 69%
“…(2) Roastees' salient, as well asmore generallyrecognized physical features, including evident disabilities or artefacts, should play a preponderant role in jibes, coinciding with or affecting their referents. It is also interesting to verify whether the taboo topic of serious disability/illness does become the referent often, leading to dark humor (see Dynel and Poppi 2018) to which disabled roastees expose themselves. (3) Attributed features are likely to be more common as the referents in Roasts of targets with no evident, let alone salient, features.…”
Section: Methodsmentioning
confidence: 99%